2016
DOI: 10.1111/pops.12344
|View full text |Cite
|
Sign up to set email alerts
|

The Differential Effects of Stress on Voter Turnout

Abstract: While everyone deals with stressful situations on a daily basis, individuals have different behavioral reactions to that stress. We argue that life stress also affects individuals' political behavior, but this effect is contingent on their past political involvement. While individuals familiar with and engaged in the political process are unaffected when confronted with stress in life, individuals who are not routinely involved in the electoral process are more likely to disengage from politics. To test the di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
28
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(28 citation statements)
references
References 55 publications
0
28
0
Order By: Relevance
“…Within the healthcare setting, Wass et al found that proxy voting as a voter facilitator instrument can increase voter turnout for those suffering from ill health or disability [47]. Hassell and Settle ran an interventional study that induced life stressors on patients and found that increasing stress decreased likelihood to vote for typical nonvoters [44]. Liggett et al conducted an evaluation of clinician-led, nonpartisan voter registration drives over 12 weeks within two university-affiliated health centers in the Bronx, New York [45].…”
Section: Healthcare Interventions Exist To Increase Voting and Democrmentioning
confidence: 99%
“…Within the healthcare setting, Wass et al found that proxy voting as a voter facilitator instrument can increase voter turnout for those suffering from ill health or disability [47]. Hassell and Settle ran an interventional study that induced life stressors on patients and found that increasing stress decreased likelihood to vote for typical nonvoters [44]. Liggett et al conducted an evaluation of clinician-led, nonpartisan voter registration drives over 12 weeks within two university-affiliated health centers in the Bronx, New York [45].…”
Section: Healthcare Interventions Exist To Increase Voting and Democrmentioning
confidence: 99%
“…When it comes to cognitive resources, early studies have noted that economic strife focuses people's attention on the most pressing material problems, such as applying for social benefits, borrowing money or moving into cheaper housing; hence less time, energy and attention are available for matters that are unrelated to economic struggles, including public affairs (Jahoda, Lazarsfeld & Zeisel 1972;Rosenstone 1982). More recent research shows that economic hardship and the attendant anxiety diminish cognitive resources to devote to non-economic concerns (Hassell & Settle 2017;Levine 2015;Marx & Nguyen 2016). When people feel anxious, they are less able to engage in adaptive behaviour patterns (Eysenck, Derakshan, Santos & Calvo 2007), compromising their ability to pay attention to incoming information (Wegbreit, Franconeri & Beeman 2014), retain such information (Eysenck & Calvo 1992) or process it optimally (Leon & Revelle 1985).…”
Section: Information Acquisition During Economic Downturnsmentioning
confidence: 99%
“…To understand how informed citizens are in times of economic upheaval, we first distinguish between economic hardship at the individual level and an economic recession at the macro level, and then consider explicitly their interaction. When economic hardship is experienced personally, it puts a strain on citizens' cognitive resources and motivation to engage in politics (Hassell and Settle 2017;Levine 2015;Marx and Nguyen 2016;Solt 2008), thus likely resulting in lower levels of information. A far-reaching macroeconomic crisis, however, is likely to trigger alarm and generate grievances about poor macroeconomic conditions among the general public, far and beyond those who are directly affected by the crisis (cf.…”
mentioning
confidence: 99%
“…For example, French, Smith, Alford, Guck, Birnie, and Hibbing () demonstrate a relationship between stress, measured by cortisol levels, and voting behavior. Similarly, Settle and Hassell () find that nonpolitical life stressors can reduce political participation among low‐propensity voters. This research presents a nice foundation for the idea that individuals will avoid engaging in behaviors that might contribute to uncomfortable feelings, such as stress.…”
Section: Selection Into Homogeneous Political Discussion Networkmentioning
confidence: 95%